CFD Analysis on Eurofighter Typhoon at Canard - Sudhakar Uppalapati, K. Veera Raghavulu, A Nishanth Kumar, Pithani Bhargav Sai Teja (International Journal of Advanced Science and Technology, 2020)
Eurofighter is of two engines, agile combat aircraft of one seat to be used for air to air and air to surface strike. Eurofighter Typhoon has a foreplane delta plan, which is naturally and purposefully aerodynamically unstable in subsonic flight and developed with pilots to give enhanced maneuverability while as yet being profoundly natural to fly. It was able to produce the most interaction robust flow duck to the main wing. The use of the elevator assigned fib, pattern slip, and flow around the wings. The use of duck can improve the lift of the aircraft and function to delay the restoring flow over the wing must have new experienced turbulence in laminar so that the hunter can handle an Angle of attack (AOA) without stalling. It is identified that the canard design of a fighter plays a crucial role. This study analyses the fluid flow around a Eurofighter Typhoon canard wing to determine the 2-Dimensional canard perform on the changes in the Angle of attack (AoA). This research was conducted using the Computational Fluid Dynamics (CFD) method because it had high accuracy and cost-effectiveness. From this study, we obtain the results of fluid flow analysis around the canard (2-Dimensional Aerofoil).